IL-7 and CCR2b Co-Expression-Mediated Enhanced CAR-T Survival and Infiltration in Solid Tumors - Li, Guangchao; Zhang, Qing; Han, Zeping; Zhu, Yangmin; Shen, Huijuan; Liu, Zhi; Zhou, Zhao; Ding, Wen; Han, Siqi; He, Jinhua; Yin, Zhao; Zhou, Jie; et al. (Frontiers in Oncology, 2021)
Chimeric antigen receptor T (CAR-T) cells are not effective in solid tumor treatment due to reduced invasion and expansion, and short survival time. This study aimed to explore whether interleukin (IL)-7 and CCR2b expression could improve GD2-CAR-T cell survival and infiltration in neuroblastoma and melanoma treatment. IL-7 and CCR2b were inserted into the classical second-generation CAR structure to construct 7×2b CAR. The 7×2b CAR-T cell phenotypes were evaluated by flow cytometry and the chemokine levels by ELISA. The 7×2b CAR-T cell migration and anti-tumor abilities were detected by Transwell assay and animal experiments in vivo. We report that compared with that of CAR-T cells, 7×2b CAR-T cell IL-7 secretion and CCR2b expression did not affect the T cell surface expression of CAR or CAR-T specificity and efficacy against tumor cells. The 7×2b CAR-T cells could induce IFN-γ secretion in GD2-positive tumor cells, killing them as well as conventional CAR-T cells. Moreover, IL-7 and CCR2b co-expression enhanced the 7×2b CAR-T cell survival and migration. Similar to conventional CAR-T, 7×2b CAR-T cells could also inhibit tumor growth and increase IFN-γ, Gzms-B, and IL-2 expression. Finally, unlike in mice injected with CAR-T cells, CD3 expression was the most abundant in the spleen and tumor tissues in mice injected with 7×2b CAR-T cells. Our study demonstrates that IL-7 and CCR2b co-expression in GD2-CAR-T cells exhibit stronger anti-tumor activity than classical second-generation CAR-T cells, shedding light on the potential novel GD2-positive neuroblastoma and melanoma treatment approach.